2002
DOI: 10.4049/jimmunol.168.10.5047
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1- and Phosphotyrosine-Independent Inhibitory Signaling by a Killer Cell Ig-Like Receptor Cytoplasmic Domain in Human NK Cells

Abstract: Killer cell Ig-like receptors (KIR) are MHC class I-binding immunoreceptors that can suppress activation of human NK cells through recruitment of the Src homology 2-containing protein tyrosine phosphatase-1 (SHP-1) to two immunoreceptor tyrosine-based inhibitory motifs (ITIMs) in their cytoplasmic domains. KIR2DL4 (2DL4; CD158d) is a structurally distinct member of the KIR family, which is expressed on most, if not all, human NK cells. 2DL4 contains only one ITIM in its cytoplasmic domain and an arginine in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 51 publications
9
147
2
1
Order By: Relevance
“…The ubiquitous transcription of the KIR2DL4 gene in the NK cell clones of all analyzed individuals and its conservation in evolution suggest that the product of this gene could essentially contribute to the biology of human NK cells, a view further supported by its distinct structure and signaling properties [11,14,16,17,22,23]. Preferential expression of the KIR2DL4 ligand, HLA-G, in the placenta pointed to a possible participation of KIR2DL4 in the poorly understood function of uterine NK cells in the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The ubiquitous transcription of the KIR2DL4 gene in the NK cell clones of all analyzed individuals and its conservation in evolution suggest that the product of this gene could essentially contribute to the biology of human NK cells, a view further supported by its distinct structure and signaling properties [11,14,16,17,22,23]. Preferential expression of the KIR2DL4 ligand, HLA-G, in the placenta pointed to a possible participation of KIR2DL4 in the poorly understood function of uterine NK cells in the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, HLA-G and, perhaps, HLA-C can be recognized directly by uterine NK cells through LILRB1; in addition, the leader peptides of those MHC molecules can be presented by HLA-E to NK cell clones expressing CD94/NKG2 heterodimers [9,10,[45][46][47]. However, none of the aforementioned receptors has signaling properties or distributions similar to those reported for KIR2DL4 [11,14,[22][23][24]. By contrast, KIR3DL3, whose ligand and functionality are unknown, shares with KIR2DL4 having a single ITIM and being well conserved in different individuals of several primate species [32][33][34][48][49][50].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22 However, it has been found that ITIM might associate with SHP-2 regardless of its phosphorylation status. 31 SHP-2 is a likely mediator of the cellular functions of CD155, since a dominant negative SHP-2 inhibits cell migration and FAK dephosphorylation after ligand stimulation of cellular CD155. 22 In addition, SHP-2 has been implicated in activation of Ras/MAPK signaling pathways and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…CD16 ECD-The CD16A (CD16) extracellular domain was subcloned from the retroviral vector pBMN-IRES-EGFP (a kind gift of Dr. Sei-ich Yusa and Dr. Kerry Campbell, Fox Chase Cancer Center, Philadelphia, PA) (50) and into the pSec Tag2/Hygro A mammalian expression vector (Invitrogen, Corp). This plasmid contained an Ig -chain leader sequence located 5Ј to the CD16 cDNA as a means to induce secretion of the expressed CD16 ECD protein into the cell supernatant.…”
Section: Cloning Expression and Purification Of Minibody Constructsmentioning
confidence: 99%